Update on the Crosstalk Between Adipose Tissue and Mineral Balance in General Population and Chronic Kidney Disease - Karava, Vasiliki; Christoforidis, Athanasios; Kondou, Antonia; Dotis, John; Printza, Nikoleta (Frontiers in Pediatrics, 2021)
Adipose tissue is nowadays considered as a major endocrine organ, which apart from controlling lipid metabolism, displays a significant role in energy expenditure, food intake and in the regulation of various systemic physiological processes. Adipose derived pro-inflammatory cytokines and adipokines, particularly leptin and adiponectin, provide inter-communication of adipose tissue with various metabolic pathways, ultimately resulting in a complex network of interconnected organ systems. Recent clinical and experimental research has been focused on exploring the direct interaction between adipokine profile and elements of mineral metabolism, including parathormone (PTH), fibroblast growth factor-23 (FGF23) and calcitriol. The emerging crosstalk between adipose tissue and calcium and phosphorus homeostasis suggests that metabolic disorders from one system may directly affect the other and vice versa. It is current knowledge that fat metabolism disturbance, commonly encountered in obese individuals, influences the expression of calciotriopic hormones in general population, while various clinical trials attempting to successfully achieve body fat loss by modulating mineral profile have been published. In chronic kidney disease (CKD) state, there is an increasing evidence suggesting that mineral disorders, presenting early in the course of the disease, influence adipose tissue and linked endocrine function. On the contrary, the impact of disturbed fat metabolism on CKD related mineral disorders has been also evocated in clinical studies. Recognizing the pathogenetic mechanisms of communication between adipose tissue and mineral balance is critical for understanding the effects of metabolic perturbations from the one system to the other and for identifying possible therapeutic targets in case of disrupted homeostasis in one of the two connected systems. To that end, this review aims to enlighten the recent advances regarding the interplay between mineral metabolism, fat mass and adipokine profile, based on in vitro, in vivo and clinical studies, in general population and in the course of CKD.